Case report: Malignant vasovagal reflex syndrome during percutaneous transcatheter closure of patent foramen ovale - Li, Zhiyang; Dong, Qian; Huang, Lun; Zeng, Qiutang; Yu, Kunwu (Frontiers in Cardiovascular Medicine, 2023)
Malignant vasovagal reflex syndrome can be induced by pulling of cardiac tissue during percutaneous transcatheter closure of patent foramen ovale. In this case, a patient presented with a malignant vasovagal reflex syndrome characterized by decreased heart rate, cardiac arrest, and ventricular tachycardia. Therefore, it’s particularly important to observe patients' heart rate and timely deal with vasovagal reflex syndrome during the operation.